Analysis Of A Signalized Intersection Using The PKJI 2023 Method And PTV Vissim 22 Modeling (Case Study: Jl. Kedung Cowek – Jl. Kenjeran – Jl. Putro Agung) - Oktaviana, Riska Oktaviana; Putra, Kurnia Hadi; Chandra Agusdini, Theresia Maria; Sekartadji, Ratih Sekartadji (Faculty of Civil Engeneering and Planning - ITATS, 2025)
Signalized intersections or traffic light control systems (APILL) are important elements in urban road networks that function to regulate vehicle flow to be more orderly and safe. The Kedung Cowek Road, Kenjeran Road, and Putro Agung Road intersection is a signalized intersection with high traffic volume and serves as a strategic junction point in the North Surabaya area. This research aims to analyze the performance of the intersection using the Indonesian Road Capacity Guidelines (PKJI) 2023 method, as well as model and simulate improvement alternatives using PTV Vissim version 22 software. The analysis stages begin with collecting daily traffic volume data, intersection geometric data, and existing signal control data. The data is analyzed using the PKJI 2023 method to obtain capacity values, degree of saturation, delay, and queue length for each approach. The existing condition analysis results show that several approaches experience a degree of saturation exceeding the ideal threshold (0,85) as well as high delays. As a solution, simulations of several alternatives were conducted, namely signal phase rearrangement, approach widening, and flyover construction from Kedung Cowek Road to Kenjeran Road. Simulation with PTV Vissim shows that flyover construction can significantly reduce the degree of saturation and delays compared to existing conditions and other alternatives. Therefore, the combination of the PKJI 2023 method and microsimulation is considered effective as a planning basis for improving signalized intersection performance.